Ag-doped phosphate glass with high weathering resistance for RPL dosimeter. (January 2021) - Iwao, Masaru; Takase, Hironori; Shiratori, Daiki; Nakauchi, Daisuke; Kato, Takumi; Kawaguchi, Noriaki; Yanagida, Takayuki
Abstract: Ag-doped phosphate glass employed in the commercial dosimeter named FD-7 is used globally as one of the most reliable dosimeter materials. The luminescence phenomenon is well known as radiophotoluminescence (RPL). In this work, a new RPL glass material was developed for dosimeters that are used under high humidity conditions. The glass material that contains Ag2 O as an activation center was produced by the melt-quenching method. The radiation properties and the optimal amount of Ag2 O concentration required for achieving the best performance of the glass were evaluated using the RPL read-out system employing the photon counting method. On exposure to UV laser light radiation, the new RPL glass developed in this work emitted light of an approximate wavelength of 650 nm after radiation exposure, and the RPL intensity was proportional to the exposed dose. In addition, the glass material exhibited high reusability owing to the repeated operation of irradiation and reset. On conducting the weathering resistance test for a long duration, it was found that the new RPL glass exhibited the same RPL intensity and appearance as its initial values. Highlights: New radiophotoluminescence (RPL) glass for dosimeter in high humidity conditions. RPL signals satisfactorily sustained for 50 days at 40 °C and 90% relative humidity. RPL read-out system for a glass dosimeter established.